?ELECTROCAPILLARY AND FLOTATION STUDIES USING POTASSIUM ETHYLXANTHATE, DITHIOPHOSPHATE COLLECTORS AND THEIR MIXTURE. (Biological Sciences - PJSIR, 2003)
The sufrace tension measurements were carried out on dropping mercury electrode (dme) in 0.1 M sodium tetraborate buffer solution, with potassium ethylxanthate (KEtx) and dithiophosphate (Dtp) added separately or in combination under comparable conditions. The electrocapillary curves determined as function of potential indicating reduction in surface tension by the addition of KEtx and Dtp. Synergistic behaviour was also studied by comparing the decrease in surface tension of individual collectors with that of their mixtures at various mole ratios and potentials. Flotation studies were also conducted on heazlewoodite (Ni3S2) with these collectors separately and in combination to study the synergistic effect.